CTGF induces tenogenic differentiation and proliferation of adipose‐derived stromal cells. Issue 3 (28th February 2019) - Li, Xiaoning; Pongkitwitoon, Suphannee; Lu, Hongbin; Lee, Chang; Gelberman, Richard; Thomopoulos, Stavros
ABSTRACT: Intrasynovial tendons are paucicellular and hypovascular, resulting in a poor response to injury. Surgical repair of ruptured or lacerated tendons often lead to complications such as adhesions, repair site gapping, and repair site rupture. Adipose‐derived stem cells (ASCs) have shown promise for enhancing tendon repair, as they have the capacity to differentiate into tendon fibroblasts and augment the healing response. Furthermore, connective tissue growth factor (CTGF) has been shown to promote tendon regeneration via the stimulation of endogenous tendon stem cells. Here, we evaluated the potential of CTGF to promote tenogenic differentiation of ASCs in vitro. Gene and protein expression, cell proliferation, and FAK and ERK1/2 signaling were assessed. CTGF increased tenogenic genes in mouse ASCs in a dose‐ and time‐dependent manner. Western blot and immunostaining analyses demonstrated increases in tenogenic protein expression in CTGF‐treated ASCs at all timepoints studied. CTGF increased ASC proliferation in a dose‐dependent manner. CTGF induced phosphorylation of ERK1/2 within 5 min and FAK within 15 min; both signals persisted for 120 min. Blocking FAK and ERK1/2 pathways by selective inhibitors SCH772984 and PF573228, respectively, attenuated the CTGF‐induced tenogenic differentiation and proliferation of ASCs. These results suggest that CTGF induces tenogenic differentiation of ASCs via the FAK and ERK1/2 pathway. Statement of clinical significance: Although prior research has led to advances in tendon operative techniques and rehabilitation methods, clinical outcomes after tendon repair remain variable, with high rates of repair site gapping or rupture. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res